New insights into solvent-induced structural changes of 13C labelled metal–organic frameworks by solid state NMR. Issue 62 (15th July 2019) - Rauche, Marcus; Ehrling, Sebastian; Krause, Simon; Senkovska, Irena; Kaskel, Stefan; Brunner, Eike
Abstract : The proposed 13 C isotope-labelling scheme enables the in-depth analysis of site-specific host–guest interactions and adsorption complexes formed in MOFs. Abstract : Selective 13 C-labelling of carboxylate carbons in the linker molecules of flexible metal–organic frameworks (MOFs) makes solid-state NMR spectroscopy very powerful to investigate solvent-induced local structural changes as demonstrated by 13 C and 1 H NMR spectroscopy on the pillared layer MOF DUT-8(Ni). Selective identification of polar solvent–node interactions becomes feasible.